Radiomics in the differential diagnosis of glioblastoma under the primary neurooncoimaging conditions - Nikita E. Maslov; Daria A. Valenkova; Alexander M. Sinitсa; Gennadiy E. Trufanov; Vladimir M. Moiseenko; Alexander Yu. Efimtsev; Vera V. Chernobrivtseva (Анналы клинической и экспериментальной неврологии)
Introduction. According to the 2021 WHO Classification of Tumors of the Central Nervous System (CNS) and the 2023 Clinical Practice Guidelines on the Drug Management of Primary CNS Cancers, the first step of molecular genetic testing to identify the morphological type and malignancy of adult-type diffuse gliomas is the detection of isocitrate dehydrogenase (IDH) mutation status. However, tumor tissue biopsy as the conventional diagnostic standard has a number of limitations that can potentially be mitigated by applying the principles of radiomics to the interpretation of magnetic resonance (MR) images.